Comprehensive long‐term efficacy and safety of recombinant human alpha‐mannosidase (velmanase alfa) treatment in patients with alpha‐mannosidosis. Issue 6 (3rd May 2018) - Lund, Allan M.; Borgwardt, Line; Cattaneo, Federica; Ardigò, Diego; Geraci, Silvia; Gil‐Campos, Mercedes; De Meirleir, Linda; Laroche, Cécile; Dolhem, Philippe; Cole, Duncan; Tylki‐Szymanska, Anna; Lopez‐Rodriguez, Monica; et al.
Abstract: Introduction: Long‐term outcome data provide important insights into the clinical utility of enzyme replacement therapies. Such data are presented for velmanase alfa in the treatment of alpha‐mannosidosis (AM). Methods: Patient data ( n = 33; 14 adults, 19 paediatric) from the clinical development programme for velmanase alfa were integrated in this prospectively‐designed analysis of long‐term efficacy and safety. Patients who participated in the phase I/II or phase III trials and were continuing to receive treatment after completion of the trials were invited to participate in a comprehensive evaluation visit to assess long‐term outcomes. Primary endpoints were changes in serum oligosaccharide and the 3‐minute stair climb test (3MSCT). Results: Mean (SD) treatment exposure was 29.3 (15.2) months. Serum oligosaccharide levels were significantly reduced in the overall population at 12 months (mean change: –72.7%, P < 0.001) and remained statistically significant at last observation (−62.8%, P < 0.001). A mean improvement of +9.3% in 3MSCT was observed at 12 months ( P = 0.013), which also remained statistically significant at last observation (+13.8%, P = 0.004), with a more pronounced improvement detected in the paediatric subgroup. No treatment‐emergent adverse events were reported leading to permanent treatment discontinuation. Conclusions: Patients treated with velmanase alfa experienced improvements in biochemical and functional measures that were maintained for up to 4 years. Long term follow‐up is important and further supports the use of velmanase alfa as an effective and well‐tolerated treatment for AM. Based on the currently available data set, no baseline characteristic can be predictive of treatment outcome. Early treatment during paediatric age showed better outcome in functional endpoints.